INDIAN TEA TRADE IN CENTRAL ASIA (SECOND HALF OF THE 19TH - BEGINNING OF THE 20TH CENTURY) - Маматова М. Б. (TARIXIY TADQIQOTLAR, 2025)
The presented scientific article analyzes the history of the Indian tea trade in Central Asia in the second half of the 19th - early 20th centuries. Based on sources and archival materials, the author of the article provides information that Peshawar merchants controlled the trade in Indian tea, who also sold various varieties of Indian green tea. The article also contains information about the duty on tea, which was increased by local authorities in order to stop the import of Indian tea to Central Asia. Based on the chronological framework of the study, this scientiufic article also focuses on the analysis of events related to the tea trade in the 20th century. Thus, according to the author, first-class Chinese tea, including, was sold as Indian tea, and from beginning of the 20th century, only Indian black teas were imported to the Turkestan region.